The leucine biosynthetic pathway is crucial for adaptation to iron starvation and virulence in Aspergillus fumigatus. Issue 1 (1st January 2019) - Orasch, Thomas; Dietl, Anna-Maria; Shadkchan, Yana; Binder, Ulrike; Bauer, Ingo; Lass-Flörl, Cornelia; Osherov, Nir; Haas, Hubertus
ABSTRACT: In contrast to mammalia, fungi are able to synthesize the branched-chain amino acid leucine de novo . Recently, the transcription factor LeuB has been shown to cross-regulate leucine biosynthesis, nitrogen metabolism and iron homeostasis in Aspergillus fumigatus, the most common human mold pathogen. Moreover, the leucine biosynthetic pathway intermediate α-isopropylmalate (α-IPM) has previously been shown to posttranslationally activate LeuB homologs in S. cerevisiae and A. nidulans . Here, we demonstrate that in A. fumigatus inactivation of both leucine biosynthetic enzymes α-IPM synthase (LeuC), which disrupts α-IPM synthesis, and α-IPM isomerase (LeuA), which causes cellular α-IPM accumulation, results in leucine auxotrophy. However, compared to lack of LeuA, lack of LeuC resulted in increased leucine dependence, a growth defect during iron starvation and decreased expression of LeuB-regulated genes including genes involved in iron acquisition. Lack of either LeuA or LeuC decreased virulence in an insect infection model, and inactivation of LeuC rendered A. fumigatus avirulent in a pulmonary aspergillosis mouse model. Taken together, we demonstrate that the lack of two leucine biosynthetic enzymes, LeuA and LeuC, results in significant phenotypic consequences indicating that the regulator LeuB is activated by α-IPM in A. fumigatus and that the leucine biosynthetic pathway is an attractive target for the development of antifungal drugs.